Ciliary body medulloepithelioma treated with intra-operative brachytherapy after fine needle aspiration biopsy - Ortiz-Seller, Amparo; Martínez-Costa, Rafael; Calatayud, José; Palacios, Inmaculada; Hernández, Ana; González, Honorio (Journal of Contemporary Brachytherapy, 2022)
Medulloepithelioma is the second most common type of pediatric intra-ocular tumors. It commonly arises from ciliary body, and it is generally diagnosed in the first decade of life. Management options for medulloepithelioma include enucleation, resection, or radiotherapy, but further investigation is still needed. Herein, we report a case of a 1-year-old girl with a ciliary body mass highly suggestive of medulloepithelioma, which caused recurrent acute episodes of intense pain. Fine needle aspiration biopsy (FNAB) of ciliary body mass was performed with trans-scleral approach, and treatment with a iodine-125 brachytherapy COMS10 plaque was undertaken during the same interventional procedure. Lesion was treated using a plaque brachytherapy, with total radioactivity of 13.5 mCi distributed in 5 seeds with immediate disappearance of pain episodes and decrease of tumor size. This is the first case of medulloepithelioma treated with brachytherapy plaque after an extemporaneous anatomo-pathological examination in children with favorable response. We consider that intra-operative brachytherapy therapy after FNAB in selected ocular tumors may be safe and effective therapeutic option, but longer follow-up is needed to confirm safety and applicability of this approach in a larger group of patients.